The Impact of Internal and External LOC with Intrinsic Motivation as a Mediator on the MSME’s Business Performance in Indonesia - Purbasari, Rr Niken; Sugiharjo, R Joko; Oli'i, Irene Adicia (Universitas Mercu Buana, 2025)
Objectives: This research explores the impact of internal and external locus of control (LOC) and mediating role of intrinsic motivation on business performance’s MSME owners in Indonesia.Methodology: This study employs Structural Equation Modelling (SEM) for quantitative analysis. The sample includes 157 MSME owners in Indonesia, selected through convenience sampling.Finding: The findings reveal that internal LOC influences business performance, with intrinsic motivation enhancing this effect as a mediator. Conversely, external LOC does not impact business performance, and intrinsic motivation does not mediate its effect. This indicates that MSME owners with a strong internal LOC tend to achieve better business performance, especially when driven by intrinsic motivation.Conclusion: The originality of this study concludes the truth of the EEP Theory, which explains role of entrepreneurial motivation in relationship between the influence of LOC with business performance. Its empirical findings strengthen previous research, and provide a perspective that confirms that generally business owners have an intrinsic motivation orientation with high internal LOC, they see and have a strong belief that business success is something that is under their control and is reinforced by the motive to achieve success. In contrast, their external LOC is low and has no influence on their intrinsic motivation and business performance.